2021
DOI: 10.1111/meta.12519
|View full text |Cite
|
Sign up to set email alerts
|

The analytic‐continental divide in philosophical practice: An empirical study

Abstract: Philosophy is often divided into two traditions or camps: Analytic Philosophy and Continental Philosophy. Characterizing the so-called "Analytic-Continental divide," however, and explaining the differences between these two philosophical traditions is no easy task. Some philosophers have argued that the differences have to do with the place of argument in the two traditions. This raises the following questions: Is Analytic Philosophy rife with arguments while Continental Philosophy is devoid of arguments? Or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These pairs were changed and pattern search was run across the entire corpus to generate a list of the articles which contained matches. While it may not seem intuitive to search for root-anchor argument indicator pairs across the whole corpus, this technique was employed in an earlier study (Mizrahi and Dickinson 2021). It was a simpler task to filter through all articles containing matches, rather than to drill down to the authors used in this study and then compile the matched articles.…”
Section: Text Mining Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These pairs were changed and pattern search was run across the entire corpus to generate a list of the articles which contained matches. While it may not seem intuitive to search for root-anchor argument indicator pairs across the whole corpus, this technique was employed in an earlier study (Mizrahi and Dickinson 2021). It was a simpler task to filter through all articles containing matches, rather than to drill down to the authors used in this study and then compile the matched articles.…”
Section: Text Mining Methodsmentioning
confidence: 99%
“… Ashton and Mizrahi (2018, p. 58) use a similar methodology to test the hypothesis that "philosophy is a priori and in the business of discovering necessary truths from the armchair." See alsoMizrahi and Dickinson (2021).…”
mentioning
confidence: 99%
“…Analytic philosophy differs from philosophical approaches that aim to provide grand frameworks about the world and the meaning of life. Also, the analytic tradition is contrasted with the continental tradition, although results from a recent empirical study of scholarly publications showed no significant difference in style of argumentation (deductive, inductive, or abductive) between the philosophical approaches (Mizrahi & Dickinson, 2021). The analytic approach is used to fix, at least temporarily, the meanings of concepts to draw distinctions and consider consequences of assumptions.…”
Section: Analytic Philosophy and Nursing Languagementioning
confidence: 99%
“…Analyses of such argumentation skills are being conducted in various subjects around the world (a.o. Sriraman & Umland, 2014;Songsil, Pongsophon, Boonsatien & Clarke, 2019;Mizrahi & Dickinson, 2020).…”
Section: Introductionmentioning
confidence: 99%